Farmer-managed natural regeneration: how to regenerate pasture and farmland on a low budget - Abdirizak H; Gudka M; Kibor B; Kinuthia M; Kimeu, P.; Leeuw, Jan de; Maimbo M; Safriel U; Njenga M; Iiyama, Miyuki (World Agroforestry Centre, 2013)
This brief is intended for project-level practitioners – extension agents, farmer trainers, leaders of farmers’ groups, pastoralist associations and others – who wish to increase the productivity of (semi-arid) pasture and farmlands using trees. The methods presented have been used on a very large scale in some West African countries – especially in southern Niger. They have also been implemented in central Tanzania (Shinyanga Region) and northern Ethiopia (Tigray – exclosures), by land owners and community groups with a strong desire to return their land to a more productive state.